Chemoresistance Transmission via Exosome-Transferred MMP14 in Pancreatic Cancer - Li, Xinyuan; Li, Kai; Li, Mengmeng; Lin, Xiaoyu; Mei, Yu; Huang, Xuemei; Yang, Huanjie (Frontiers in Oncology, 2022)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest malignancies. Gemcitabine is the most commonly used chemothepy for the treatment of PDAC, but the development of drug resistance still remains challenging. Recently, exosomes have emerged as important mediators for intercellular communication. Exosomes affect recipient cells’ behavior through the engulfed cargos, however the specific cargos responsible for gemcitabine resistance in PDAC are poorly understood. Here, we reported that exosomes could transfer gemcitabine resistance via a metalloproteinase 14 (MMP14)-dependent mechanism. MMP14 was identified as a major differentially secreted protein from the gemcitabine-resistant PDAC cells by comparative secretome. It was packaged into the exosomes and transmitted from the chemoresistant cells to the sensitive ones. The exosome-transferred MMP14 could enhance drug resistance and promotes the sphere-formation and migration abilities of the recipient sensitive PDAC cells. Mechanically, exosome-transferred MMP14 promotes the stability of CD44，the cancer stem cell marker in the recipient cells. Our results indicate that MMP14 is a key player for exosome-mediated transfer of gemcitabine resistance, thus targeting MMP14 in exosomes may represent a novel strategy to limit gemcitabine resistance in PDAC.